Mild Microfluidic Approaches to Oxide Nanoparticles Synthesis. Issue 9 (16th December 2021) - Zardi, Paolo; Carofiglio, Tommaso; Maggini, Michele
Abstract: Oxide nanoparticles (oxide NPs) are advanced materials with a wide variety of applications in different fields. The use of continuous flow methods is particularly appealing for their synthesis due to the high control achieved over the reaction conditions and the easy process scalability. The present review focuses on the preparation of oxide NPs using microfluidic setups at low temperature (≤80 °C), since the employment of mild reaction conditions is crucial for developing sustainable and cost‐effective processes. A particular emphasis will be put on the improvement over the final product features (e. g., size, shape, and size distribution) given by flow methods with respect to conventional batch procedures. The main issues that arise by treating NPs suspensions in microfluidic systems are product deposition or channel clogging; mitigation strategies to overcome these drawbacks will also be presented and discussed. Abstract : This review reports the preparation of oxide nanoparticles in microreactors under continuous flow conditions. The use of suitable methodologies allows to manage the size and shape of the nanoparticles, through the fast mixing of the reagents and the precise control of the reaction conditions that can be achieved within flow devices, if compared to batch syntheses.